Հեքիաթի դասավանդումը միջին դպրոցում համագործակցային (ինտերակտիվ) ուսուցմամբ - Յարամիշյան, Միրա
В статье, согласно требованием новой общеобразовательной системы, рассматривается преподавание жанра сказки, в частности, в 5 классе, на основе интерактивного метода обучения, приводя конкретный пример предусмотренной программы, по разделу «С неба упало 3 яблока» по первой сказке «Не рой другому яму, сам в нее попадешь». The article deals mainly with the fairy tale genre teaching particularly in the fifth for on the basis of the interactive method of teaching on demands of the new educational system based on the example in accordance with the curriculum referring to the unit «Tree apples fell from the sky» and Chickens come home to roost ». Համագործակցային ուսուցման ժամանակ սովորողները, համագործակցելով փոքր խմբերով, ձևավորում են ընդհանուր հասկացություններ և հմտություններ: Աշակերտները համագործակցային միջավայրում են կառուցում իրենց հմտությունները`խոսելու, բացատրելու, բանակցելու, վիճարկելու և հարցեր տալու միջոցով: The article deals mainly with the fairy tale genre teaching particularly in the fifth for on the basis of the interactive method of teaching on demands of the new educational system based on the example in accordance with the curriculum referring to the unit «Tree apples fell from the sky» and Chickens come home to roost».
Keywords: Հայոց լեզվի դասավանդման մեթոդիկա